AN EXPERIMENTAL STUDY ON SPINNING DISC KEY PARAMETERS INFLUENCING ITS PERFORMANCE - IACOB-TUDOSE, Eugenia Teodora (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The spinning disc technology (SD), with its enhanced fluid flow features, has been applied to an increasing number of fields lately. Experimental characterization of the flow on a smooth or radially/concentrically indented rotating disc, for different feeding liquid flow rates (30, 50, 70 L/h) and disc rotational speeds (200, 500, 800, 1100 rpm), using two types of feed distribution systems (one nozzle or four symmetrically distributed nozzles) has been performed, based on the pulse response technique. Based on the radial dispersion model, the Péclet number was determined for different experimental conditions and used to identify flow characteristics and to compare different spinning disc setups efficiencies. Based on the obtained experimental data, the large flowrate values and disc rotational speeds induce a flow regime closer to plug flow, however intense micromixing is achieved within an intermediate range of the studied parameters, when the turbulent wavy liquid film surface occurs, the micromixing is increased and thus, the SD technology is efficiently used. Certain flow characteristics can be achieved if the spinning disc is operated at specific parameter values.